f(x) = xe^-x
f'(x) = (1)e^-x + x[e^-x(-1)]
= e^-x-xe^-x
= -e^-x(x-1)
So,
f''(x) = [-e^-x(-1)] (x-1)+ (-e^-x)(1)
= e^-x (x-1)-e^-x
= e^-x(x-2)
Now, f''(x) = e^-x(x-2) is continuous on its domain, (-oo, oo), so the only way it can change sign is by passing through zero. (The only partition numbers are the zeros of f''(x))
f''(x) = 0 if and only if either e^-x=0 or x-2 = 0
e to any (real) power is positive, so the only way for f'' to be 0 is for x to be 2.
We partition the number line:
(-oo, 2) and (2,oo)
On the interval (-oo,2), we have f''(x) < 0 so f is concave down.
On (2,oo), we get f''(x) >0, so f is concave up.
Inflection point
The point (2, f(2)) = (2,2/e^2) is the only inflection point for the graph of this function.